SARS-CoV-2 evolution within and between individuals - Koelle, Katia (Henry Stewart Talks, 2021)
Evolutionary factors driving emergence of SARS-CoV-2 variants, Metrics of SARS-CoV-2 infections: virus numbers per transmission event, Potential co-infection with 2 or more variants per transmission event, Current understanding of the origin and evolution of recent variants, Impact of vaccines and treatments on evolutionary pressures of SAR-CoV-2